MEDICAL-BIOLOGICAL PROPERTIES OF ZINC LYSINATE-RIBOFLAVINATE - Andrew Vladimirovich Blinov; Vladimir Alexandrovich Orobets; Elena Sergeevna Kastarnova; Alexander Vladimirovich Serov; Julia Jurievna Snezhkova; Svetlana Nikolaevna Solovieva (Вестник Северо-Кавказского федерального университета, 2022)
The biomedical properties of the zinc-lysinitroboflavinate - new colloidal chelate form of zinc trace microelement are investigated within the framework of the work. Intragastric administration of 100 mg / kg of zinc lysinate-riboflavinate to experimental animals does not cause signs of toxicological effects. Toxicological tests of zinc lysinate-riboflavinate were carried out on the basis of the Department of Therapy and Pharmacology of the Faculty of Veterinary Medicine of StSAU. The disperse phase composition of zinc lysinate-riboflavinate aqueous solutions was investigated by the method ofphoton-correlation spectroscopy in the laboratories of the Department of Technology of Nanomaterials (NCFU, Engineering Institute).